Development and evaluation of a telehealth videoconferenced support group for rural spouses of individuals diagnosed with atypical early-onset dementias. (May 2014) - O'Connell, Megan E; Crossley, Margaret; Cammer, Allison; Morgan, Debra; Allingham, Wendy; Cheavins, Betty; Dalziel, Donna; Lemire, Maurice; Mitchell, Sheri; Morgan, Ernie
Atypical and early-onset dementias can be particularly problematic for family caregivers, and support groups aimed at memory loss and Alzheimer's disease are not always helpful. Unfortunately, little has been developed specifically for caregivers of individuals with atypical dementias such as the frontotemporal dementias. Compounding the lack of access to interventions targeted specifically at caregivers of individuals with atypical and early-onset dementias are the unique needs of rural caregivers. Due to the relative infrequency of these particular dementias and the large geographical distances between rural caregivers, technology-facilitation is required for any group-based intervention. This paper describes the development of a secure telehealth videoconferenced support group for rural spouses of individuals with atypical and early-onset dementias. In addition, we provide preliminary evidence of effectiveness and describe a template for future groups based on the key therapeutic aspects of this novel technology-facilitated intervention.